Peningkatan Layanan Pembelajaran Aktivitas Motorik Bagi Anak Dispraksia Dengan Model Circuit Game - Indahwati, Nanik; Kurrotun Ainin, Ima; Dwi khory, Fifukha; Kartiko, Dwi Cahyo; Romadhon, Nurman (Universitas Negeri Surabaya, 2025)
This program focused on providing motor activity learning support for children with developmental coordination disorder (dyspraxia). The goal was to enhance teachers’ understanding and skills in creating learning experiences that are enjoyable, innovative, and accessible for students with special needs. The approach involved introducing the circuit game model, which integrates fine and gross motor movements into a structured sequence of activities. Socialization and mentoring sessions were conducted for Physical Education teachers at FKKGO, Mojoagung District. The program yielded positive outcomes: (1) improved teachers’ knowledge and ability to apply the circuit game model in Physical Education for children with dyspraxia; and (2) strengthened teachers’ competence in designing physical literacy activities tailored to students with special needs.